Alternative Cropping Systems with Limited Irrigation - A. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2017)
A limited irrigation study involving four cropping systems and evaluating four crop rotations was initiated at the Southwest Research-Extension Center near Tribune, KS, in 2012. The cropping systems were two annual systems (continuous corn [C-C] and continuous grain sorghum [GS-GS]) and two 2-year systems (corn-grain sorghum [CGS]) and corn-winter wheat [C-W]). In 2016, corn yields were similar in all rotations, as were grain sorghum yields. This tended to agree with the 4-yr average yields, except for average grain sorghum yields being higher following corn than grain sorghum.